Surgical Outcomes, Technical Performance, and Surgery Burden of Robotic Total Gastrectomy for Locally Advanced Gastric Cancer: A Prospective Study. Issue 5 (22nd November 2022) - Chen, Qi-Yue; Zhong, Qing; Liu, Zhi-Yu; Li, Ping; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Huang, Ze-Ning; Lin, Ju-Li; et al.
Abstract : Objective: To compare the short-term outcomes, surgery burden, and technical performance of robotic total gastrectomy (RTG) and laparoscopic total gastrectomy (LTG) for gastric cancer (GC). Summary of Background Data: The impact of robotic systems on total gastrectomy remains obscure. Methods: This prospective study included 50 patients with advanced proximal GC underwent RTG combined with spleen-preserving splenic hilar lymphadenectomy between March 2018 and February 2020. Patients who underwent LTG in the FUGES-002, http://links.lww.com/SLA/C929 study were enrolled to compare the outcomes between RTG and LTG. Results: After propensity score matching, 48 patients in the RTG group and 96 patients in the LTG group were included in the analysis. The RTG group had a lower volume of intraoperative blood loss than the LTG group (38.7 vs 66.4 mL, P = 0.042). Significantly more extraperigastric lymph nodes were retrieved in the RTG group than in the LTG group (20.2 vs 17.5, P = 0.039). The average number of errors was lower in the RTG group than in the LTG group (43.2 vs 53.8 times/case, P < 0.001). The RTG group had a higher technical skill score (30.2 vs 28.4, P < 0.001) and a lower surgery task load index (33.2 vs 39.8, P < 0.001) than the LTG group. No significant difference was found in terms of postoperative morbidity between the 2 groups (14.6% vs 16.7%, P = 0.748). Conclusions: In complex total gastrectomy for GC, compared with traditional laparoscopic surgery, robotic surgery provides a technically superior operative environment and reduces surgeon workload at high-volume specialized institutions.